Elastic Recovery Permukaan UHMWPE Berpasangan dengan Baja Tahan Karat 316L, Kobalt Khrom dan Titanium - Budi Basuki; Andhi Akhmad Ismail (Jurnal Engine: Energi, Manufaktur, dan Material, 2019)
Ultra High Molecular Weight Polyethylene (UHMWPE) is a biomedical polymer applied for orthopedic as hip, knee, ankle and lumbar disc implants. The use of this material is common as a joint component paired with metallic biomaterials such as 316L stainless steel (SS 316L), cobalt chrome alloy (CoCr) dan titanium. This application has a wear problem. UHMWPE implants are commonly made with machining processes, i.e. lathe and milling. The effect of machining is the surface roughness of implant products. Polymer highly elastic in which would induce the deformation of surface asperities during loading and unloading. This phenomenon is determined with a parameter called elastic recovery. The magnitude of elastic recovery relates to the wear of the polymer. This research numerically investigated the effect of metallic biomaterial types on the UHMWPE elastic recoveries. Those metals are CoCr, SS 316L, and titanium. Two-dimensional surface asperity models were loaded with physiological gait loads of hip and knee. Results from computational works showed an insignificant difference of UHMWPE elastic recoveries penetrated by the studied metals. Elastic recovery due to SS 316L with knee gait load is 55.19%, equal to CoCr while other results due to titanium are slightly higher, 55.224%. The difference for all metals is only 0.06 %. Contact pressures are also equal, 38.96 MPa (CoCr), 38.98 MPa (316L and titanium).